2016
DOI: 10.1590/0004-282x20160071
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits in chronic pain patients, in a brief screening test, are independent of comorbidities and medication use

Abstract: Objective To describe and analyze cognitive aspects in patients with chronic pain and a control group without pain. Method A case-control study was conducted on 45 patients with chronic pain and on 45 control subjects. Data including pain diagnosis, comorbidities and medication used, were evaluated. Cognitive tests, such as the Montreal Cognitive Assessment (MoCA), Verbal Fluency Test, Clock Drawing Test and Stroop Test, were applied. Results Patients with chronic pain showed a poorer performance, as show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 20 publications
2
26
0
6
Order By: Relevance
“…A previous study 30 reported that the patients with chronic pain had a poorer performance in the MoCA instrument (total score), Verbal Fluency Test, Clock Drawing Test and Stroop Test. The group with chronic pain also had a higher frequency of depressive disorder, generalized anxiety disorder, non-repairing sleep and hypothyroidism.…”
Section: Discussionmentioning
confidence: 88%
“…A previous study 30 reported that the patients with chronic pain had a poorer performance in the MoCA instrument (total score), Verbal Fluency Test, Clock Drawing Test and Stroop Test. The group with chronic pain also had a higher frequency of depressive disorder, generalized anxiety disorder, non-repairing sleep and hypothyroidism.…”
Section: Discussionmentioning
confidence: 88%
“…Our adapted model of CCI altered the cognitive performance in the novel object recognition though not in the Y‐maze. Pain‐related cognitive deficits in humans (Ferreira, Oliver, Thomaz, Teixeira, & Foss, ) include not only impairments in working memory, but also a worse performance in a brief screening test like the MoCA, verbal fluency, clock drawing, and stroop tests. Impairments in attention and working memory have been both found in patients suffering chronic pain.…”
Section: Discussionmentioning
confidence: 99%
“…Since many functional regions are shared for pain processing and cognitive processing, patients with chronic pain often complain cognitive impairment and inattention. 51,52 Pain-related attention and emotion are closely associated with medial temporal cortex, which is considered to be linked with pain integration and pain perception. 33 Increased grey matter volume (GMV) in the middle temporal lobes was found in postherpetic neuralgia 53 and low-back pain altered several functional brain regions including middle temporal lobes, 54,55 and a similar result was reported in burning mouth syndrome patients.…”
Section: Discussionmentioning
confidence: 99%